A novel human iPSC model of COL4A1/A2 small vessel disease unveils a key pathogenic role of matrix metalloproteinases. - Al-Thani, Maha; Goodwin-Trotman, Mary; Bell, Steven; Patel, Krushangi; Fleming, Lauren K; Vilain, Catheline; Abramowicz, Marc; Allan, Stuart M; Wang, Tao; Cader, M Zameel; Horsburgh, Karen; Van Agtmael, Tom; et al. (Elsevier BV, 2023)
Cerebral small vessel disease (SVD) affects the small vessels in the brain and is a leading cause of stroke and dementia. Emerging evidence supports a role of the extracellular matrix (ECM), at the interface between blood and brain, in the progression of SVD pathology, but this remains poorly characterized. To address ECM role in SVD, we developed a co-culture model of mural and endothelial cells using human induced pluripotent stem cells from patients with COL4A1/A2 SVD-related mutations. This model revealed that these mutations induce apoptosis, migration defects, ECM remodeling, and transcriptome changes in mural cells. Importantly, these mural cell defects exert a detrimental effect on endothelial cell tight junctions through paracrine actions. COL4A1/A2 models also express high levels of matrix metalloproteinases (MMPs), and inhibiting MMP activity partially rescues the ECM abnormalities and mural cell phenotypic changes. These data provide a basis for targeting MMP as a therapeutic opportunity in SVD.
Keywords: COL4A1/A2; Cerebral small vessel disease; blood-brain barrier; disease modelling; endothelial cells; extracellular matrix; human induced pluripotent stem cells; matrix metalloproteinases; mural cells; Humans; Induced Pluripotent Stem Cells; Endothelial Cells; Brain; Stroke; Extracellular Matrix; Matrix Metalloproteinases; Collagen Type IV